LEARNING MODELS GAME BASED LEARNING (GAME LaKaSiSiKu, LaKaTaSiSiPa, AND LaKaTaSiSiHa) INCREASING THE LEARNING MOTIVATION OF STUDENTS IN CLASS VIII OF SMP NEGERI 1 MUMBULSARI - Nurul Handayani; Ermi Purwanti; Yayuk Mulyati (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
This study was prepared with the aim of increasing student’s learning motivation using a game-based learning model through the game LaKaSiSiKu, LaKaTaSiSiPa, and LaKaSiSiHa in class VIII-C students of SMP Negeri 1 Mumbulsari, Jember, East Java Academic Year 2022/2023. The learning motivation referred to in this study, namely the activeness of students both mentally and physically. This type of research is Classroom Action Research (CAR), where students are facilitators and observers in learning. This research design uses the Kemmis and Mc. Taggart model, which is a research model consisting of four components including planning, action implementation, observation, and reflection. The research was conducted in the even semester of the 2022/2023 academic year. The research subjects were students of class VIII-C SMP Negeri 1 Mumbulsari. The object of the research is student’s earning motivation. Data collection techniques used observation and interviews. The data were analyzed descriptively and presented in the form of tables and graphs. The results showed an increase in learner motivation, in cycle I of 75.32%, then in cycle II it increased to 79.61%, and increased in cycle III by 90.09%. This means an increase of 14.77%. Thus, the use of game-based learning models in science subjects can increase the learning motivation of students in class VIII-C SMP Negeri 1 Mumbulsari.